Because Claudette - Baptiste, Tracey (Dial Books for Young Readers, 2022)
A picture book biography of Claudette Colvin, the African American girl who at age fifteen in 1955, boarded a segregated bus and was arrested for not giving up her seat to a white woman. Chronicles how this event sparked the Montgomery Bus Boycott, which eventually led to the Supreme Court decision that made the state of Alabama's bus segregation unconstitutional.